PENERAPAN STRATEGI PREVIEW, QUESTION, READ, SUMMARIZE, TEST (PQRST) UNTUK MENINGKATKAN KETERAMPILAN MEMBACA INTENSIF DI KELAS IV SD - Cut Marlini (Program Studi Pendidikan Guru Sekolah Dasar, 2018)
The purpose of this study was to improve intensive reading skills through Preview, Question, Read, Summary, and Test(PQRST) learning strategies for the fourth grade students of elementary school (SDN 45) Bungo Pasang Padang. The design of this study was classroom action research carried out in two cycles, which cycle consisting of planning, implementation, observation, and reflection. The research subjects of this study were teachers and students of the fourth grade of SD Negeri 45 Bungo Pasang. The data were collected quantitatively and qualitatively obtained by testing, observation and documentation techniques. Data analysis techniques used were qualitative descriptive analysis and quantitative descriptive analysis technique. The results of the study show that: (1) The use of PQRST strategies increase the activeness of the fourth grade students of SDN 45 Bungo Pasang. (2) The use of PQRST strategies shows the increase in students' intensive reading skills which the result of the pre-action test shows only 15 out of 25 have achieved completeness or only 60% of students completed, an increase to 80% in cycle I or as many as 20 of 25 students completed, and increased to 90% in cycle 2 or 24 of 25 students completed . Abstrak Tujuan penelitian ini adalah meningkatkan keterampilan membaca intensif melalui strategi pembelajaran PQRST pada siswa IV SD Negeri 45 Bungo Pasang Padang. Rancangan penelitian ini menggunakan penelitian tindakan kelas yang dilaksanakan dalam dua siklus, setiap siklus terdiri atas perencaan, pelaksanaan, observasi, dan refleksi. Subyek penelitian adalah guru dan siswa kelas IV SD Negeri 45 Bungo Pasang. Jenis data berupa data kuantitatif dan kualitatif yang diperoleh dengan teknik tes, observasi, dan dokumentasi. Teknik analisis data menggunakan teknik analisis deskriptif kualitatif dan analisis deskriptif kuantatif. Hasil penelitian menunjukkan: (1) Penggunaan strategi PQRST dapat meningkatkan keaktifan siswa kelas IV SDN 45 Bungo Pasang. (2) Penggunaan strategi PQRST juga menunjukkan adanya peningkatan keterampilan membaca intensif siswa. Dimana tes pratindakan menunjukkan hanya 15 dari 25 saja yang mencapai ketuntasan atau hanya sebesar 60 % siswa tuntas, terjadi peningkatan menjadi 80% pada siklus I atau sebanyak 20 dari 25 siswa tuntas, dan meningkat menjadi 90% pada siklus 2 atau 24 dari 25 siswa tuntas. Kata Kunci: keterampilan membaca intensif,strategi belajar, PQRST